ADSORPTION OF TARTRAZINE ON POLYANILINE-WATER HYACINTH COMPOSITE - Jaleel Shanshool Tahar, Hussein Ismail Abdullah (Chelonian Research Foundation, 2023)
Abstract The study focused on the adsorptive elimination of Tartrazine from water based solutions using a Polyaniline-Water Hyacinth nanocomposite. The influence of contact time dye concentration at the start, pH, and dosage of adsorbent on the percentage elimination of Tartrazine dye was examined. Enhance in pH and dosage of adsorbent, along with a reduction in first dye concentration, resulted in higher E102 dye removal. The Polyaniline-Water Hyacinth nanocomposite was prepared and characterized using EDX, XRD, SEM and BET techniques. XRD analysis validated the polycrystalline nature of the prepared Polyaniline-Water Hyacinth nanocomposite. Equilibrium data was collected at different temp (25°C, 45°C, 55°C and 35°C,) and examined utilizing Temkin, Isotherms of Langmuir, Dubinin-Radushkevich and Freundlich. Kinetic data was also examined utilizing second order of pseudo, first order of pseudo, Diffusion of intra particles, and Elovich models. The diffusion of intra particle model revealed a linear connection (R2 = 0.92showing that pore diffusion is a limiting phase in the entire adsorption process. The adsorption process was further investigated at different temp (25°C, 45°C 35°C, and 55°C) to obtain thermodynamic factors for the adsorption system.. Keywords: Adsorption, Tartrazine, Polyaniline-Water Hyacinth (PANI-WH), Nanocomposite